AB0363 Coadministration of asp015k, a novel janus kinase inhibitor, with methotrexate demonstrates tolerability and lack of pharmacokinetic interactions in patients with rheumatoid arthritis. (23rd January 2014) - Zhu, T.; Oda, K.; Valluri, U.; Moore, B.; Cao, Y.; Chindalore, V.; Akinlade, B.
Abstract : Background: ASP015K is an oral Janus kinase (JAK) inhibitor with selectivity for JAK1/3 in development for treatment of rheumatoid arthritis (RA) and other autoimmune diseases. Methotrexate (MTX) is the most common nonbiologic DMARD therapy and is recommended as first-line therapy in RA treatment guidelines. In humans, MTX is primarily excreted unchanged in urine. Transporter-mediated renal tubular secretion of MTX is thought to be a major mechanism of pharmacokinetic (PK) drug-drug interactions. Objectives: In vitro experiments were performed to evaluate the effects of ASP015K on renal transporters. A clinical drug-drug interaction study in RA patients evaluated the effects of multiple-dose ASP015K on MTX PK and the short-term safety and tolerability of coadministration. Methods: In vitro experiments assessed the inhibitory potency of ASP015K on human multidrug resistance-associated protein 2/4 (MRP2/4) and organic anion transporter 1/3 (OAT1/3). A phase 1, open-label, single-sequence study was conducted to confirm the in vivo effect of ASP015K on the PK of MTX, a substrate of MRP2/4 and OAT1/3. 15 patients diagnosed with RA for ≥6 months who had been treated with MTX (15–25 mg weekly) for ≥28 d were enrolled. Patients received their usual prescribed dose of MTX on day 1. They then received ASP015K 100 mg BID for 6.5 d (days 3–9 [morning]) and a second prescribed dose of MTX in combination with ASP015K on day 8. Serial blood samples were collected for MTX concentrations after dosing on day 1 (MTX alone) and 8 (MTX+ASP), and for ASP015K concentrations after dosing on day 7 (ASP alone) and 8 (MTX+ASP). Predose ASP015K concentrations (Ctrough ) were measured on days 3–8. Urinary excretion of MTX and ASP015K was assessed. Results: ASP015K demonstrated no in vitro inhibitory effect on MRP2/4 or OAT1 (IC50 >100 µM); it inhibited OAT3 with an IC50 of 5 µM. 14 patients completed the phase 1 study for PK evaluation. Results showed that MTX exposure was not affected by coadministration of ASP015K; AUCinf ratio (MTX+ASP/MTX alone) was 103% [90% CI, 93–113]; Cmax ratio was 92% [90% CI, 83–103]. Analysis of Ctrough indicated ASP015K levels reached steady state on day 5. ASP015K AUC12, ss was not affected by coadministration of MTX with a ratio (MTX+ASP/ASP alone) of 98% [90% CI, 91–106]. ASP015K Cmax decreased by 8% with a ratio (MTX+ASP/ASP alone) of 92% [90% CI, 78–108], which was considered not to be clinically significant. The unbound Cmax of ASP015K at 100 mg BID was estimated to be <1/10th of the IC50 for OAT3 in vitro, suggesting that ASP015K would not affect MTX PK. ASP015K was well tolerated when coadministered with MTX. One patient experienced a SAE (urinary tract infection) before receiving study drug and subsequently a second SAE (gastroenteritis) after receiving MTX on day 1 but before receiving ASP015K. This patient was withdrawn. Conclusions: Coadministration of ASP015K and MTX was well tolerated in this short-term study, exhibiting no clinically significant effect on the PK profile of either drug. Efficacy and safety of ASP015K/MTX combination therapy is being assessed in ongoing phase 2 trials in RA patients. Disclosure of Interest: T. Zhu Employee of: Astellas Pharma Global Development, Inc., K. Oda Employee of: Astellas Pharma Inc., U. Valluri Employee of: Astellas Pharma Global Development, Inc., B. Moore Employee of: Astellas Pharma Global Development, Inc., Y. Cao Employee of: Astellas Pharma Global Development, Inc., V. Chindalore: None Declared, B. Akinlade Employee of: Astellas Pharma Global Development, Inc.